Singularidades e subjetividades de um grupo do PIBID na área de matemática: contribuições para o processo de formação de identidade professoral - Conceição, Eressiely Batista Oliveira (2019)
This research presents a study carried out on one of the programs of the current educational policy regarding the initial formation of teachers, especially in the potential of the Program of Initiation to Teaching (PIBID), as a space for the construction of the teaching identity. In addition to seeking to understand the sense that scholarship recipients (ID) attribute in their Relation with Knowledge for the construction of professorial identity, in this process of formation. In order to do so, we have the target audience for the research, graduates in Mathematics of the Federal University of Sergipe / Campus São Cristóvão (UFS / SC), being they scholarship recipients corresponding to the edict of the period 2014 to 2018. Among them, a focus group was formed with 10 graduates who at the time belonged to one of the subgroups of the PIBID area of Mathematics / UFS / SC. When we followed this process of teacher education in Mathematics graduates, some questions emerged, arriving at the central question of research: What is the meaning and meaning of which scholarship recipients of PIBID teaching in the area of Mathematics / UFS / SC attribute to their process of teacher training when participating in this program? To answer this question, we had as a theoretical basis the assumptions of Bernard Charlot's Relation with Knowing (1979, 2005, 2006, 2013), seeking to associate his ideas with the assumptions of Fleck (2010) about styles of thought. Other authors also subsidized the study, constituting it in qualitative nature as participant research. The methodological procedures were exploratory and descriptive, with the perspective of identifying and analyzing how the actions of the scholars studied contribute to a sense of their formative process, with singularities and subjectivities.Also, it was observed how the figures of the learning of these subjects are established for the exercise of the teaching profession. In the course of the research, the data collection consisted of questionnaire, observation and participation in meetings and workshops of Mathematics (extension project), documentary analysis (records, articles and reports), logbook and interviews at the focus group meetings. Data analysis was systematized by the identification of relevant words that constituted subcategories and categories, as a form of constellations that gave representativeness to the meanings and meanings attributed by the subjects of the research. That is, for these subjects, the meaning attributed to PIBID implies the singularities that are represented by the subcategories worked in the process of analysis, such as the mathematical knowledge and area of performance; Learning; Activity; Exercise of Teaching; Collectivity; Production; Uniqueness of the group. Relationships narrowed as categories on the relation with knowledge that instituted in this space of formation, give meaning to the ID scholarship holders in participating in the PIBID program, were: the social relation with knowledge itself (mathematical), in turn implying in the epistemic dimensions , identity and social (relationship with the other and with oneself), as well as the mobilizational disposition with knowledge, the desire to learn to be teachers of Mathematics, to do scientific research, and to act with extension actions. In these relationships the subjectivities of these ID scholarships are established, under a singular collective of the group itself, which generates a Collective of Thought.